2018
DOI: 10.5603/cj.a2017.0103
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure with recovered ejection fraction: Clinical characteristics, determinants and prognosis. CARDIOCHUS-CHOP registry

Abstract: Patients with HF and reduced LVEF who were re-evaluated after 1 year, had significant improvement in their LVEF and had a more favourable prognosis than HF with preserved and reduced ejection fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
39
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 29 publications
8
39
4
Order By: Relevance
“…In the multivariate analysis, carrying an ICD was the only independent variable significantly associated with a lower probability of LVEF recovery (HR 0.25, 95% CI 0.13-0.47, p < 0.0001). This finding has already been observed in previous studies [10,11,20] and may be related to the fact that an ICD is recommended to reduce the risk of sudden death and all-cause mortality in patients with symptomatic HF (NYHA classes II-III) and an LVEF ≤35% despite ≥3 months of optimal medical therapy [5]. Consequently, patients with an ICD in our cohort were more likely to have a diagnosis of chronic HF much earlier in time to the others, thus entailing a lower probability of LVEF recovery.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the multivariate analysis, carrying an ICD was the only independent variable significantly associated with a lower probability of LVEF recovery (HR 0.25, 95% CI 0.13-0.47, p < 0.0001). This finding has already been observed in previous studies [10,11,20] and may be related to the fact that an ICD is recommended to reduce the risk of sudden death and all-cause mortality in patients with symptomatic HF (NYHA classes II-III) and an LVEF ≤35% despite ≥3 months of optimal medical therapy [5]. Consequently, patients with an ICD in our cohort were more likely to have a diagnosis of chronic HF much earlier in time to the others, thus entailing a lower probability of LVEF recovery.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to the etiology of ventricular dysfunction, previous ischemic heart disease has been associated with a lower probability of ventricular function recovery [7,9,10,20]. In our study, this condition was more common among patients in group NR (57.2 vs. 46.8%), although the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In addition, the study demonstrated that not carrying an ICD or cardiac resynchronization therapy predicted LVEF recovery. These results are similar to those published by Agra-Bermejo et al [2]. These data may be important before planning device implantation, and require further research to better stratify those HF-recovered patients that do not necessitate an implantable cardioverter defibrillator.…”
supporting
confidence: 88%
“…However, the predictors of recovery do not seem to be clearly established. Agra-Bermejo et al [2] showed that treatment with ACE inhibitors and beta-blockers was an independent predictor of LVEF recovery. The effects of sacubitril-valsartan on LV remodeling have been uncertain.…”
mentioning
confidence: 99%